Designing Effective Language Tests: A Framework for Integrating Stages, Processes, and Best Practices - Pandey, Gopal Prasad (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Educational settings rely on language testing to obtain essential data about students' language skills and to inform teaching approaches. This study investigates a structured methodology for developing effective language tests by examining their fundamental stages: design, operationalization, and administration. It emphasizes the importance of combining validity, reliability, authenticity and practicality throughout the test development process to improve assessment outcomes. A conceptual and descriptive methodology is employed, combining theoretical perspectives with empirical evidence and established best practices in language assessment. This paper outlines essential steps of test development which involve defining test objectives, selecting formats, writing items, piloting and administering the test. In this study, the core stages of test development are systematically analyzed, encompassing defining the purposes of the test design, selecting formats, writing items, piloting, and administering the test. The key findings reveal that test development is an iterative and cyclical process that requires constant feedback and revisions. Additionally, the findings indicate that integrating formative assessment with technological advancements improves both test accuracy and efficiency. Hence, the study offers a comprehensive framework for creating language assessments while identifying key best practices along with important ethical guidelines.